The Algerian public banks in the era of the digital transformation - Ibtissem BOUACHERIA KEBIR; Tarik SALHI (المجلة الدولية للأداء الاقتصادي, 2023)
Lately, new Information and Communication Technologies ICTs have hugely developed. Their impact on the banks, has been great. Thus, this paper takes a sample of the Algerian public banks in the city of Oran as case study using a questionnaire in order to show their level of engagement and maturity regarding the digital transformation and use of digital technologies. Findings that the Algerian public banks are interested in making up for their late joining of the digital world.